Perbandingan Kata Zongsuan, Suanshi, Zhongyu, Jieguo Serta Padanan Katanya dalam Bahasa Indonesia - Jesica Merryl Gilbert; Septerianie Sutandi (Jurnal Bahasa dan Sastra, 2021)
This research discussed the comparison of the words zǒngsuàn 总算, suànshì 算是, zhōngyú 终于, jiéguǒ 结果 in Chinese language and their equivalent words in Indonesian language. These four words are the words which show the time description of an event. The writer chose to analyze there four words because of the semantic similarity of the four words. Three of the words have the same meaning and one other word has a similar meaning. In addition, Pleco digital dictionary app translates the four words into 'finally', which means ‘akhirnya’ in Indonesian language (KBBI, 2016) and classifies them all in the same class of words, the adverbs. This research used descriptive qualitative method and literature study data collection techniques. The results showed that the four words have sameness in grammatical location, channel of communication, final result, and word equivalency. Furthermore, it was also found that these four words have several differences in terms of word class, grammatical location, channel of communication, process, final result, and word equivalency.